2020
DOI: 10.1021/acsnano.0c03095
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Head-to-Head Hairpin DNA Dimerization Is Essential for the Synthesis of Orange Emissive Silver Nanoclusters

Abstract: DNA secondary structures, such as dimers and hairpins, are important for the synthesis of DNA templateembedded silver nanoclusters (DNA/AgNCs). However, the arrangement of AgNCs within a given DNA template and how the AgNC influences the secondary structure of the DNA template are still unclear. Here, we introduce a noncanonical head-to-head hairpin DNA nanostructure that is driven by orange-emissive AgNCs. Through detailed in-gel analysis, sugar backbone switching, inductively coupled plasma mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…[44] Ac oncurrent study on the same type of 6C hairpin systems has confirmed the presented findings and provides further insight into the detailed requirements for formation of self-assembly of emissive hairpin dimers. [45] Angewandte Chemie Forschungsartikel Figure 5. SAXS data (*)a nd predictions( blue lines) from the molecular models of the 6C-miR-21-10bp AgNC-DNA dimer (right) and unmodified monomer (left).…”
Section: Resultsmentioning
confidence: 99%
“…[44] Ac oncurrent study on the same type of 6C hairpin systems has confirmed the presented findings and provides further insight into the detailed requirements for formation of self-assembly of emissive hairpin dimers. [45] Angewandte Chemie Forschungsartikel Figure 5. SAXS data (*)a nd predictions( blue lines) from the molecular models of the 6C-miR-21-10bp AgNC-DNA dimer (right) and unmodified monomer (left).…”
Section: Resultsmentioning
confidence: 99%
“…Bene顒僼ing from the important role of the third and fourth cytosines in the C-loop in base 顒刬pping, the two six-C-loop structures form head-to-head dimers via the cytosine-Ag-cytosine bridge a顐漞r 顒刬pping base to implement the formation of orange emissive AgNCs 43,44 (no. 7 in Table 2).…”
Section: Secondary-structure-dependent Formation Of Agncsmentioning
confidence: 99%
“…In recent years, some approaches revealed that the formation of AgNCs depend largely on the speci顒僣 secondary structure by interaction of the protonation, base-pairing, and cluster-DNA, further highlighting the role of the secondary structure in regulating the properties of AgNCs. [40][41][42][43][44] Consequently, it is necessary to integrate recent progresses with the acknowledged mechanism and summarize again the direct link between the silver atom organization on the DNA secondary structure and the performance of AgNCs, and the stimuli-responsive dynamic performance of AgNCs based on the change of the DNA secondary structure, providing an all-round support for understanding the origin of DNA/AgNCs.…”
mentioning
confidence: 99%
“…In addition, the relationship between the structural and fluorescence emission of DNA-AgNCs was also studied. Recently, Shah et al (2020) reported that the orange emitting AgNCs were localized on the interface via a headto-head binding of two DNA hairpins, while green, red, or NIR emissive AgNCs were embedded in a hairpin and double stranded DNA templates. The hairpin DNA can convert into G-quadruplex (G 4 ) or i-motif structures, while the G 4 -AgNCs only showed intense peaks and the i-motif AgNCs exhibited poor peaks (Li et al, 2011).…”
Section: Factors Affecting the Fluorescence Of Dna-agncsmentioning
confidence: 99%